Aspectos cognitivos do transtorno obsessivo-compulsivo - Torres, Albina Rodrigues [UNESP] (My University, 1998)
This paper describes the most important cognitive models for obsessive-compulsive disorder, i. e., the inference processes (thoughts and believes) underlying the patients'feelings and behaviors. The major models formulated in this area emphasize the following aspects: exacerbated perception of danger (risk evaluation), overimportance of intrusive thoughts, excessive sense of personal responsibility (blame for harm self and others), perfectionism, psychological fusion of thought and action, and illogical inference processes involving confusion between imagination and reality. The knowledge of cognitive aspects brings new perspectives for the psychological treatment of this disorder.
Cognitive aspects for obsessive-compulsive disorder
Keywords: Cognitive aspects; Cognitive therapy; Obsessive-compulsive disorder